Assessing the risks of children with preoperative comorbidities undergoing comminuted fracture surgery - Cheng, Kai-Yuan; Yang, Chen-Yu; Liu, Shih-Chia (Frontiers in Pediatrics, 2023)
Comminuted fractures are characterized by bones broken in at least two places, destabilizing the bone and requiring surgery. Children whose bones are still developing and maturing tend to have a higher risk of sustaining comminuted fractures as the result of trauma. Trauma is a major cause of death in children and constitutes a major issue in orthopedics because of the unique properties of children’s bones compared to adult bones and the associated complications. This retrospective, cross-sectional study aimed to refine the association between comorbid disease and comminuted fractures in pediatric subjects using a large, national database. All data were extracted from the National Inpatient Sample (NIS) database from 2005 to 2018. A total of 2,356,483 patients diagnosed with comminuted fractures were selected initially, of whom 101,032 patients aged younger than 18 years who underwent surgery for comminuted fractures were included. Logistic regression analysis was used to evaluate associations between comorbidities and comminuted fracture surgery and between various comorbidities and LOS or unfavorable discharge. Study results suggest that patients with any comorbidities undergoing orthopedic surgery for comminuted fracture appear to have longer LOS and a higher proportion of discharge to long-term care facilities. Almost all comorbidities were significantly associated with poor in-hospital outcomes and longer LOS. The analysis of comminuted fractures in children may provide useful information to help first responders and medical personnel evaluate and manage comminuted fractures appropriately.